Performance of gradient porous structures in hydrodynamics and heat transfer in hydrogen production carriers. (24th January 2020) - Chen, Xiangyang; Liu, Jie; Fan, Yanbin; Zhou, Yinglong
Abstract: We propose a theoretical method based on experience and inference and improved the temperature formula for the fluid flow in a porous structure in order to improve the efficiency of porous catalytic carrier of methanol hydrogen production. The comparison between linear gradient porous structure and fixed gradient porous structure is the purpose of this paper. The present work deals mainly with some impact factors which include porosity, Reynolds number, Fluid velocity, Fluid pressure, Nusselt number, Plante number, heat transfer coefficient of fluid convection and Fluid temperature. There are three major findings. First, wet-cycle proportional factor control equations were introduced to further improve the temperature formula. Second, fluid mixing of the gradient porous structure is more sufficient, relative to the fixed gradient porous structure. Third, the fluid temperature of the gradient porous structure drops more rapidly relative to the fixed gradient porous structure. These findings contribute to improved aspects of porous catalytic carriers. Highlights: Wet-cycle proportional factor control equations were introduced to further improve the temperature formula. Gradient-changing models had a much greater change in velocity than the fixed-gradient model. The pressure in the fixed-gradient model was less than that in the gradient-changing models. The convective heat transfer coefficient of the gradient-changing models was larger than that of the fixed-gradient model.